Improve WiMAX performance using directional antennas and resource management algorithms - Banna, Hussam Ahmad (Journal of engineering sciences and information technology, 2022)
using directed antennas in a WiMAX network, with the standard method of connection between the SS subscriber station and the RS Relay station which was based on the distance between nodes, becomes useless. Hence, we need for a new method of linking different from its being dependent on distance, It is not necessary for a user to link with nearest relay station. Since the new method will not adopt a standard based on distance, it was necessary to consider a set of new standards aimed at comprehensively improving network efficiency, such as increasing throughput, reducing network delay and reducing interference during link assignment SS-RS. The first search expansion algorithm has been proposed to form a tree structure that directs the communication path between subscriber and base station through relay stations in a multi-hop network scenario. Then a second algorithm was proposed that works to achieve load balancing between relay stations, and finally a third algorithm was proposed that directs the stations ’radiation according to the path of minimum interference. the opnet modular program was used to implement and analyze the performance of the proposed algorithms, and the results showed a remarkable improvement in throughput and minimizing delay, which are the two main metrics of measuring network performance.